2021
DOI: 10.1021/acs.nanolett.0c04004
|View full text |Cite
|
Sign up to set email alerts
|

Grain-Boundary-Engineered La2CuO4 Perovskite Nanobamboos for Efficient CO2 Reduction Reaction

Abstract: Electroreduction of carbon dioxide (CO 2 RR) has been regarded as a promising approach to realize the production of useful fuels and to decrease greenhouse gas levels simultaneously, where highefficiency catalysts are required. Herein, we report La 2 CuO 4 nanobamboo (La 2 CuO 4 NBs) perovskite with rich twin boundaries showing a high Faraday efficiency (FE) of 60% toward ethylene (C 2 H 4 ), whereas bulk La 2 CuO 4 exhibits a FE CO of 91%. X-ray absorption spectroscopy (XAS) reveals that the Cu in La 2 CuO 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 34 publications
8
69
0
Order By: Relevance
“…Thetemperatures for desorption of chemisorbed CO 2 of these samples were about 307.4 8 8C( L 2 C), 325.7 8 8C( L 1.9 C), 307.9 8 8C (L 1.8 C), and 292.7 8 8C( L 1.7 C), indicating that the CO 2 chemisorption strength was enhanced in the following order:L 1.7 C < L 1.8 C % L 2 C < L 1.9 C. It was previous suggested that, the chemisorption of CO 2 on the catalyst surface was ak ey prerequisite for the CER, and its strength was positively correlated with the CER property. [15] As shown in Figure 6d, we calculated the FE ratios of CER/H 2 of these catalysts,with the values of 2.78 (L 2 C), 3.78 (L 1.9 C), 2.83 (L 1.8 C), and 1.3 (L 1.7 C). As expected, these values resembled the trend of CO 2 chemisorption strength (Figure 6d), further reinforcing the strong correlation between CO 2 chemisorption and CER property of the catalysts.B esides,b yu sing CO-TPD,w e evaluated the CO adsorption behaviors on these catalysts (Figure 6e).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thetemperatures for desorption of chemisorbed CO 2 of these samples were about 307.4 8 8C( L 2 C), 325.7 8 8C( L 1.9 C), 307.9 8 8C (L 1.8 C), and 292.7 8 8C( L 1.7 C), indicating that the CO 2 chemisorption strength was enhanced in the following order:L 1.7 C < L 1.8 C % L 2 C < L 1.9 C. It was previous suggested that, the chemisorption of CO 2 on the catalyst surface was ak ey prerequisite for the CER, and its strength was positively correlated with the CER property. [15] As shown in Figure 6d, we calculated the FE ratios of CER/H 2 of these catalysts,with the values of 2.78 (L 2 C), 3.78 (L 1.9 C), 2.83 (L 1.8 C), and 1.3 (L 1.7 C). As expected, these values resembled the trend of CO 2 chemisorption strength (Figure 6d), further reinforcing the strong correlation between CO 2 chemisorption and CER property of the catalysts.B esides,b yu sing CO-TPD,w e evaluated the CO adsorption behaviors on these catalysts (Figure 6e).…”
Section: Methodsmentioning
confidence: 99%
“…Given the above,D FT calculations were performed to predict the CER properties of the L 2Àx Ccatalysts.T oconform the actual structure and composition of the L 2Àx Cseries as far as possible,t he DFT calculations were implemented on the L 2 C(111), oxygen-vacancy-contained L 2 C(111) (labelled as O v -L 2 C(111)) and CuO/L 2 C(111) surfaces. [15,25] Noting that the A-site cation deficiency was not considered in our models, because the A-site cations typically did not play as the active sites toward catalysis. [31] Since the HER competed with the CER during electrolysis,w ef irst evaluated the Gibbs free energy profiles for HER in alkaline solution on the three surfaces (Figure 4a)toclarify whether the oxygen vacancy or CuO could suppress the HER.…”
Section: Forschungsartikelmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 110 ] The density functional theory calculations revealed that the intrinsic strain between the (113) surfaces in La 2 CuO 4 can increase the bond length of Cu‐O and Cu‐La, resulting in the enhanced selectivity toward C 2 H 4 . [ 110 ]…”
Section: Electrocatalysis Of Co2rrmentioning
confidence: 99%
“…[ 109 ] More recently, Huang and co‐workers reported that the valence state of Cu in La 2 CuO 4 nanobamboo remained unchanged during electrocatalysis. [ 110 ] On the basis of these reports, we can reason that the phase changes of La 2 CuO 4 , including surface amorphization, should relate to the conditions of bulk electrolysis and the catalyst‐electrolyte interface, while further detailed studies are needed to tune the selectivity and maintain the stability. In short, further in‐depth researches of Cu‐containing perovskite oxides would allow precise structural manipulation of the Cu‐containing perovskite oxide and facilitate the rational design of this important type of CO 2 RR catalysts.…”
Section: Electrocatalysis Of Co2rrmentioning
confidence: 99%